Tantangan Menggunakan Sistem Informasi Geografi Di Indonesia−Aplikasi Kematian Ibu - Sulistyawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Maternal Mortality Rate (MMR) is number of mother deaths per 100.000 live births. MMR is one important value that must be considered by all country in the world, it is because MMR is one how to measure a success of the country related to MDGs point 5. The use of Geographic Information System (GIS) in health sector has been very large; however, especially in maternal mortality this application is still limited.Objective: To know the development of geographic information systems applications over the last ten years.Method:This review based on several research articles mainly focus on GIS application related to maternal mortality.Result: This paper identified several issues in application GIS related to maternal mortality; one of which is data availability is not good that makes GIS can’t give his best performance.Conclusion: The conclusion of this paper that some applications related to maternal mortality has been applied in various part of the world included Indonesia, for example, mapping of maternal mortality distribution and spatial analysis of maternal mortality.Keywords: Geographic Information System, Maternal Mortality Rate